Measuring Value Relevance of Accounting Information (A comparative study on the banks listed in the Damascus and Beirut Stock Exchanges) (Journal of Hama University, 2024)
The research aims to test, measure and compare the relevance of the value of accounting information using the modified Ohlson model of operating cash flows in the Damascus and Beirut Stock Exchanges.The statistical population of the study was represented by the traditional banks listed in the Damascus and Beirut Securities Exchanges, which are (11) banks in the Damascus Securities Exchange and (6) banks in the Beirut Securities Exchange, using the modified Ohlson model during the period from 2018 to 2020.The results showed that the accounting information is relevance to the value in the Beirut Securities Exchange, and that the three study models are statistically significant, and their explanatory power improved after controlling the bank size variable in the Beirut Securities Exchange, while the results showed that in the Damascus Stock Exchange there is only one statistically significant model, which is the second model ( Earnings per share and book value of equity) after controlling the bank’s size variable.
Keywords: Value Relevance, Earnings per Share, Book Value of Equity, Operating Cash Flows, Modified Ohlson Model